2018
DOI: 10.1093/annonc/mdx703
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of acquired resistance to first- and second-generation EGFR tyrosine kinase inhibitors

Abstract: Patients with non-small-cell lung cancer (NSCLC) whose tumours harbour activating mutations within the epidermal growth factor receptor (EGFR) frequently derive significant clinical and radiographic benefits from treatment with EGFR tyrosine kinase inhibitors (TKIs). As such, prospective identification of EGFR mutations is now the standard of care worldwide. However, acquired therapeutic resistance to these agents invariably develops. Over the past 10 years, great strides have been made in defining the molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
391
1
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 521 publications
(438 citation statements)
references
References 123 publications
8
391
1
4
Order By: Relevance
“…Among the 109 EGFR-TKI refractory cases in our cohort, approximately half had EGFR T790M (n = 54), while 20 additional patients (18%) showed other genetic alterations associated with TKI resistance, including rare EGFR mutations (n = 4), PIK3CA mutations (n = 4), CTNNB1 mutations (n = 3), MET mutations (n = 2) or amplification (n = 1), PDGFRA mutations (n = 2), immunhistochemically proven SCLC transformation (with TP53 mutations, n = 2), and KRAS mutation (n = 1). 59,60 In summary, our work demonstrates the feasibility and significant advantages of comprehensive, DNA-and RNA-based targeted NGS profiling of NSCLC in a routine clinical setting by presenting the largest single-institution cohort reported to date. Most of these secondary alterations prevent binding or bypass the effect of EGFR and ALK inhibitors by triggering receptor-independent downstream signaling.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Among the 109 EGFR-TKI refractory cases in our cohort, approximately half had EGFR T790M (n = 54), while 20 additional patients (18%) showed other genetic alterations associated with TKI resistance, including rare EGFR mutations (n = 4), PIK3CA mutations (n = 4), CTNNB1 mutations (n = 3), MET mutations (n = 2) or amplification (n = 1), PDGFRA mutations (n = 2), immunhistochemically proven SCLC transformation (with TP53 mutations, n = 2), and KRAS mutation (n = 1). 59,60 In summary, our work demonstrates the feasibility and significant advantages of comprehensive, DNA-and RNA-based targeted NGS profiling of NSCLC in a routine clinical setting by presenting the largest single-institution cohort reported to date. Most of these secondary alterations prevent binding or bypass the effect of EGFR and ALK inhibitors by triggering receptor-independent downstream signaling.…”
Section: Discussionmentioning
confidence: 85%
“…In the remaining resistant EGFR + and ALK + cases, disease progression was presumably due to complex mechanisms not detectable in our panel-based sequencing approach and not amenable to further TKI treatment. 59,60 In summary, our work demonstrates the feasibility and significant advantages of comprehensive, DNA-and RNA-based targeted NGS profiling of NSCLC in a routine clinical setting by presenting the largest single-institution cohort reported to date. Our results expand the prevalence of main targetable mutations reported from compiled cohorts, such as the TCGA, and highlight the additional prognostic and predictive insights gained by the simultaneous considering of cooccuring genetic alterations.…”
Section: Discussionmentioning
confidence: 85%
“…Molecular mechanisms of acquired resistance to EGFR-TKIs involve drug target alterations (e.g., EGFR T790M mutation) or bypass signaling activations (e.g., MET amplification, ERBB2 amplification). The gatekeeper T790M mutation in EGFR kinase is the most common (approximately 60%) resistance mechanism following firstand second-generation EGFR-TKI treatment (6,7). Therefore, efforts have been made to target the EGFR T790M mutation, resulting in the development of third-generation EGFR-TKIs, including rociletinib (CO-1686), olmutinib (HM61713), and osimertinib (AZD9291; refs.…”
Section: Introductionmentioning
confidence: 99%
“…31,32 However, their effectiveness is limited by the development of radioresistance and the inevitable occurrence of EGFR-TKI resistance. 33,34 They are also limited due to radiation-induced lung injury and TKI-induced interstitial lung disease. 35,36 In our study, we demonstrated that irradiation-induced NF-κB activation plays a vital role in resistance to radiotherapy and EGFR-TKIs in NSCLC.…”
Section: Discussionmentioning
confidence: 99%